KEBERLANJUTAN FUNGSI EKOLOGIS SEBAGAI BASIS PENATAAN RUANG KOTA BERKELANJUTAN - Mukaryanti, Mukaryanti (Jurnal Teknologi Lingkungan, 2006)
The pattern of the land, natural resources and environment used will influence the sustainability of a city. Nowadays, many cities in Indonesia have been developed without consideration of ecological aspects. The development of built areas that tends to be sprawling and convert natural environments such as forests and other green areas, wetlands, and lakes that have ecological functions has been causing the increasing environmental problems such as floods, groundwater shortage, and micro climate change in many cities. Spatial planning that considers thesustainability of ecological functions is a strategic tool to manage the city’s land allocation so as to achieve sustainable cities. However, most spatial planning products of cities have been made without the support of ecological data and analysis in the planning process. The paper discusses the importance of maintaining the ecological spaces as a part of an urban ecosystem and decribes the concept of sustainable spatial planning, including data and analysis should be prepared in order to integrate ecological consideration in the sustainable spatial planning process.